BRASERO: A Resource for Benchmarking RNA Secondary Structure Comparison Algorithms. (21st May 2012) - Allali, Julien; Saule, Cédric; Chauve, Cédric; d'Aubenton-Carafa, Yves; Denise, Alain; Drevet, Christine; Ferraro, Pascal; Gautheret, Daniel; Herrbach, Claire; Leclerc, Fabrice; de Monte, Antoine; Ouangraoua, Aida; et al.
Abstract : The pairwise comparison of RNA secondary structures is a fundamental problem, with direct application in mining databases for annotating putative noncoding RNA candidates in newly sequenced genomes. An increasing number of software tools are available for comparing RNA secondary structures, based on different models (such as ordered trees or forests, arc annotated sequences, and multilevel trees) and computational principles (edit distance, alignment). We describe here the website BRASERO that offers tools for evaluating such software tools on real and synthetic datasets.